Enhancing Trust and Legal Accountability in Attendance Systems Using Blockchain-Based Smart Contracts - Ramanov Muxiddin Xamrobekovich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Attendance systems are fundamental in educational institutions, workplaces, and various organizations. Traditional attendance management approaches suffer from vulnerabilities such as fraud, data tampering, and lack of legal accountability. This paper proposes a novel framework that integrates blockchain technology— specifically smart contracts—with IoT-based attendance data collection to enhance trust, immutability, and legal enforceability. By leveraging the TrustContract platform by TrustMe.uz, the system ensures tamper-proof, timestamped attendance records with legal validation. The proposed solution’s architecture, smart contract design, IoT integration, and performance evaluation are presented. Comparative analysis with manual and IoT only systems highlights significant improvements in security, privacy, and scalability. Challenges and future research directions related to privacy preservation and widespread adoption are also discussed.